"A Tenacious Reputation for Unreliability:" Re-Viewing Evliya Çelebi's Description of the Diyarbakir Ulu Cami in the Seyahatname. Issue 1 (2nd January 2020) - Andersen, Angela
Abstract: This article examines the role of seventeenth-century writer Evliya Çelebi's Seyahatname ( Book of Travels ) as an architectural source by "re-viewing" the passages pertaining to his visit to the Great Mosque of Diyarbakir in 1655. Evliya's intriguing description of a mosque with a dome does not match the surviving main prayer hall with its gabled roof. I parse the apparent discrepancies in Evliya's presentation of the physical structure by comparing his entries to other historical accounts of the mosque and placing these alongside the evidence provided by the building itself. Countering criticisms of Evliya's skills of observation, I argue instead that the Seyahatname described what the mosque meant in the context of its Ottoman Islamic history, and how it was received and understood by visitors to Diyarbakir.